An Evaluation of the Effects of Brand Equity on Consumer Willingness to Pay Price Premium - Aminu, Suleiman Garba; Ahmad, Norzieiriani (International Journal of Marketing Research Innovation, 2018)
The purpose of this study is to evaluate the outcome of brand equity on consumer responses by specifically investigating the effects of the overall brand equity on consumer willingness to pay premium price. The paper also empirically investigated the causal relationship among brand awareness, brand association, perceived quality, and brand loyalty as antecedents of brand equity. Using the automobile product category in Malaysia as stimuli, cross-sectional survey data were collected and analyzed using partial least square structural equation modeling technique. Result showed that brand equity plays a significant role in firms by creating and developing additional value to organizations and their products. A causal relationship among the antecedents of brand equity was also established. Among the antecedents of brand equity, brand loyalty was found to be the dominant driver of overall brand equity. Moreover, the effect of brand equity on consumers’ willingness to pay price premium was substantiated and found to be positive. The limitation of the paper is that the study used a single high involving product category. Future studies should use product categories with short consumption length and high purchase frequency. Findings of this study provide more insight to managers on how to manage brand equity. Outcomes of brand equity can be used to measure the performance of brand in the market. The study also provides additional clarification to the existing literature on the need for managers to develop a post-brand equity marketing strategy in order to achieve sustainable competitive advantage.